Biodegradable Cassava Starch/Phosphorite/Citric Acid Based Hydrogel for Slow Release of Phosphorus: In Vitro Study - Andrés F. Chamorro; Manuel Palencia; Enrique M. Combatt (Gels, 2024)
Phosphorous (P) is one the most important elements in several biological cycles, and is a fundamental component of soil, plants and living organisms. P has a low mobility and is quickly adsorbed on clayey soils, limiting its availability and absorption by plants. Here, biodegradable hydrogels based on Cassava starch crosslinked with citric acid (CA) were made and loaded with KH2PO4 and phosphorite to promote the slow release of phosphorus, the storing of water, and the reduction in P requirements during fertilization operations. Crosslinking as a function of CA concentrations was investigated by ATR-FTIR and TGA. The water absorption capacity (WAC) and P release, under different humic acid concentration regimens, were studied by in vitro tests. It is concluded that hydrogel formed from 10% w/w of CA showed the lowest WAC because of a high crosslinking degree. Hydrogel containing 10% w/w of phosphorite was shown to be useful to encouraging the slow release of P, its release behavior being fitted to the Higuchi kinetics model. In addition, P release increased as humic acid contents were increased. These findings suggest that these hydrogels could be used for encouraging P slow release during crop production.